2009
DOI: 10.1111/j.1365-2230.2008.02856.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic nonhealing ulcer on the hand

Abstract: A 12-year-old boy presented with a progressive chronic ulcer over the left hand of 6 yearsÕ duration. The lesion had started as a skin-coloured papule over the dorsum of the left hand. It later ulcerated and gradually extended over a number of years to the adjacent area at one end and healing with scarring at the other. This led to fusion of the middle three fingers of the left hand, causing difficulty with movement. The lesion was not preceded by any local trauma or bite. He was from poor socioeconomic backgr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Plaque-type LV is considered a common form, while based on a study done in India, the ulcerative type was the least common clinical variant, accounting for 14.2% of cases [8]. Long-standing ulcerative LV may eventually lead to scarring and deformity in addition to the risk of squamous cell carcinoma [9]. Fortunately, our patient had no destruction or deformity in the underlying tissue.…”
Section: Discussionmentioning
confidence: 75%
“…Plaque-type LV is considered a common form, while based on a study done in India, the ulcerative type was the least common clinical variant, accounting for 14.2% of cases [8]. Long-standing ulcerative LV may eventually lead to scarring and deformity in addition to the risk of squamous cell carcinoma [9]. Fortunately, our patient had no destruction or deformity in the underlying tissue.…”
Section: Discussionmentioning
confidence: 75%
“…Concomitant tuberculous infection of the spine was discovered after the patient's presentation with digital pain and swelling. 7 De et al 8 reported a 12-year-old boy with 6 years of chronic ulceration and tissue remodeling of the left hand causing fusion of the index, middle, and ring finger. The lesion was bordered on the dorsum of the hand with an atrophic, hypopigmented ''cigarette paper-like'' scar.…”
Section: Case Reportsmentioning
confidence: 99%
“…The patient was treated with isonizaide, rifampicin, ethambutol, and pyrazinamide and was markedly improved after 4 weeks. 8 Chrispal et al 9 reported a 40-year-old immunocompetent woman with fusiform swelling of the small finger of her left hand. The patient failed to improve after an initial debridement and course of antibiotics.…”
Section: Case Reportsmentioning
confidence: 99%